THE INFLUENCE OF COMPENSATION SUITABILITY, EFFECTIVENESS OF INTERNAL CONTROL, AND INDIVIDUAL MORALITY ON TENDENCY OF ACCOUNTING FRAUD - Wisnu Reno Wijaya (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2021)
This study aims to determine the effect that could be given of compensation suitability, internal control effectiveness, and individual morality to the tendency of accounting fraud. This research was conducted at Regional Apparatus Organization in Purbalingga regency and the sample in this study amounted to 31 samples using Slovin method. The collected data analyzed through multiple linear regression analyses. The result that can be obtained from this study give evidence that the suitability of compensation, the effectiveness of internal control, and the individual morality has a negative and significant influence on the tendency of accounting fraud. Base on the result in this study, Regional Apparatus Organization of Purbalingga Regency needs to pay attention to various policies related to increasing compensation conformity, the effectiveness of internal controls, and individual employee morality to reduce employee fraud tendency.